Data quality in telephone surveys and the effect of questionnaire length: A cross-national experiment - Caroline Roberts; Gillian Eva; Nick Allum; Peter Lynn (University of Essex, Institute for Social and Economic Research (ISER), 2010)
Respondents in long telephone survey interviews may adopt satisficing strategies as they approach the end of the questionnaire (Holbrook, Green and Krosnick, 2003). However, there is inconsistency regarding the relationship between questionnaire length and different forms of satisficing. We investigate whether long questionnaires are associated with a reduction in response quality using data from a cross-national survey experiment. Sample members were randomly assigned to interviews of 60, 45 or 30 minutes. We compare responses to attitudinal measures from a module on happiness and well-being, which was asked at different points in the interview in each of the three groups.
Keywords: C81; C83; 330; measurement error; respondent fatigue; prior questions; satisficing; survey error; Meinungsforschung; Telefon; Befragung; Zufriedenheit; Statistischer Fehler; Großbritannien